LEGAL PERSON AS THE SUBJECT OF CIVIL AND LEGAL RELATIONS ON THE INTERNET (CONCLUSION) - Michael V. Tarasov (Вестник Северо-Кавказского федерального университета)
In the second part of the article from the number of foreign lawsuits author examines the problem of participation of legal entities in civil relations in information and communication on the Internet and the ways of solving it.